Rock magnetism in modern soils, Buenos Aires Province, Argentina - Orgeira, Maria Julia (2008)
The influence of climate on the magnetic signal has been investigated assuming it is a first order factor in soil formation. In order to assess the degree of variability of the magnetic signal under different drainage conditions, Mollisols from the Pampean region developed on Pampean loess at varying topographical positions were studied. The sampled sites were located south and north of Buenos Aires in Verónica and Zárate, Pampa Ondulada. The magnetic signal is opposite in the two areas. The generation of superparamagnetic particles (SP) seems to be higher in Zárate. The loss of detrital magnetite could be higher in the less drained soils, in agreement with the hypothesis of loss of detrital magnetite by reductive process. As a simplified interpretation, it is suggested that the differential soil humidity in the studied soils could explain their different magnetic signal. The degree of drainage seems to be the variable that conditions the process of reduction loss.